(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rapid evolution in information technology, software, and hardware equipment has greatly affected emerging and improving new education approaches called E-learning. Universities and stakeholders have stepped forward and started investing in this learning type to increase higher education revenue. On the other hand, students become greedy to join online learning regardless of geographical area, students’ ethnicity, and age. The scholars showed that online learning outperformed face-to-face education to obtain knowledge and satisfy their needs. However, some challenges could face online learning, such as the sense of isolation as students are virtually connected and technology could be difficult for most students. This study highlights online literature, challenges, and, on top of that, giving recommendations to enhance a quality of e-learning